The Making of the Modern Iranian Capital - Elmira Jafari (A+BE: Architecture and the Built Environment)
This dissertation puts together planning documents and multiple archival sources to demonstrate how urban planning and the role of planners have evolved in an ever-changing transnational context of Iran. It challenges the prevailing approach in the literature of Tehran urban studies that simply flattens the complexity of local-foreign collaboration and labels transnational planning of Tehran a top-down “Westernization” project. To depict a more nuanced picture of Tehran master planning at the time of transnational exchange and rapid urban growth, this dissertation introduces a new engaging and argumentative periodization with four distinct phases which brings transnational planning of Tehran to the fore, while reflecting on diverse political and socio-economic upheavals between 1930-2010. Dissection of Tehran master plans in each period through the lens of multiple actors offers a unique opportunity for a renewed interpretation of transnational planning of Tehran and the way Iranian planners steered Tehran urban developments while engaging with foreign experts and their planning systems. It presents a detailed analysis of overarching ‘ideas’ behind each plan, their translation to urban ‘policies’ and later on their broader (un)wanted ‘impact’ on the city and its regions. By recognizing a great diversity in transnational approach in Tehran planning practices, the dissertation concludes with how transnationalism first gave rise to the formation of the modern planning system and how later on led to contestations against it which revolutionized the role of urban planners and the political agenda for Tehran urban growth.